Consensus Goals in the Field of Visual Metacognition. (November 2022) - Rahnev, Dobromir; Balsdon, Tarryn; Charles, Lucie; de Gardelle, Vincent; Denison, Rachel; Desender, Kobe; Faivre, Nathan; Filevich, Elisa; Fleming, Stephen M.; Jehee, Janneke; Lau, Hakwan; Lee, Alan L. F.; et al.
Despite the tangible progress in psychological and cognitive sciences over the last several years, these disciplines still trail other more mature sciences in identifying the most important questions that need to be solved. Reaching such consensus could lead to greater synergy across different laboratories, faster progress, and increased focus on solving important problems rather than pursuing isolated, niche efforts. Here, 26 researchers from the field of visual metacognition reached consensus on four long-term and two medium-term common goals. We describe the process that we followed, the goals themselves, and our plans for accomplishing these goals. If this effort proves successful within the next few years, such consensus building around common goals could be adopted more widely in psychological science.